Plague and public health in early modern Seville - Bowers, Kristy Wilson (Rochester studies in medical history, 2013)
This study of sixteenth-century Seville offers a new perspective on how early modern cities adapted to living with repeated epidemics of plague. Rejecting a crisis framework in favor of one of balance, it argues that city officials worked with medical professionals to successfully monitor and respond to epidemics in such a way that residents willingly cooperated with the system. In so doing, they found ways to balance the often conflicting medical and economic interests of city residents, the varied medical beliefs of physicians, and the overlapping power structures of municipal and royal gove.